2019
DOI: 10.1002/rcm.8442
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the performance of a paper‐based UV exposure sensor: The photodegradation mechanism of brilliant blue FCF in the presence of TiO2 photocatalysts in both the solid state and solution

Abstract: Rationale The decolouration of brilliant blue FCF by the action of titanium dioxide (TiO2) under ultraviolet (UV) exposure has been recently reported as the basis of a paper‐based sensor for monitoring UV sun exposure. The mechanism of brilliant blue FCF photodegradation in the presence of the photocatalyst and the resulting photoproducts are thus far unknown. Methods The UV‐initiated photodegradation of brilliant blue FCF in the presence of TiO2 for both the aqueous and the solid state was investigated. Degra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Contrary to the pH‐responsive dyes that change color upon UV‐driven acid formation, the dyes in photoactive redox state‐change‐based colorimetric UV sensors can change color upon photo‐oxidation or photoreduction. When a dye molecule is photoexcited in the presence of a semiconducting material, the latter produces free radical‐based oxidative species that can degrade the dye molecules, making them colorless 61. This aspect is well‐known in the literature as photo‐oxidation or photo‐oxidative catalysis, or sometimes even referred simply as photocatalysis 50e,62.…”
Section: Working Principles and Sensing Mechanisms Of Uv Sensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Contrary to the pH‐responsive dyes that change color upon UV‐driven acid formation, the dyes in photoactive redox state‐change‐based colorimetric UV sensors can change color upon photo‐oxidation or photoreduction. When a dye molecule is photoexcited in the presence of a semiconducting material, the latter produces free radical‐based oxidative species that can degrade the dye molecules, making them colorless 61. This aspect is well‐known in the literature as photo‐oxidation or photo‐oxidative catalysis, or sometimes even referred simply as photocatalysis 50e,62.…”
Section: Working Principles and Sensing Mechanisms Of Uv Sensorsmentioning
confidence: 99%
“…When a dye molecule is photoexcited in the presence of a semiconducting material, the latter produces free radical-based oxidative species that can degrade the dye molecules, making them colorless. [61] This aspect is wellknown in the literature as photo-oxidation or photo-oxidative catalysis, or sometimes even referred simply as photocatalysis. [50e,62] On the other hand, some dye molecules may get reduced during photoexcitation in the presence of an electron donor through a process known as photoreduction or photoreductive catalysis.…”
Section: Photoactive Redox State-change-based Colorimetric Uv Sensorsmentioning
confidence: 99%
“…As such, it is the catalyst of choice for decomposing dyes into mineralized products due to its abundance, chemical stability, good optical transparency, high refractive index, non-toxic nature, and low cost [20]. Khiabani et al [73] analyzed the photodegradation process of Brilliant Blue FCF by adding TiO 2 under UV irradiation. It was shown that, the most important oxidative pathways for the degradation of this dye involved the loss of para-methylbenzenesulfonic acid (MBSA) groups and ethyl groups adjacent to amines.…”
Section: Catalysts In Aops For Removal Of Food Dyesmentioning
confidence: 99%